2006
DOI: 10.1007/s00442-006-0429-9
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal strategies in sponge larvae: integrating the life history of larvae and the hydrologic component

Abstract: While known to be uniformly non-feeding, short-lived, and potentially short dispersing, sponge larvae display different behaviours (swimming ability and taxis). Our aim was to show whether sponge larvae with different behaviours exhibit different dispersal strategies under variable intensity of water movements. We first assessed the distribution of larvae of six taxa: Dictyoceratida spp., Dysidea avara, Crambe crambe, Phorbas tenacior, Scopalina lophyropoda, and Cliona viridis, collected through plankton sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 43 publications
3
70
0
2
Order By: Relevance
“…A significant absence of inbreeding also occurs in other geographically distant populations of this species (Blanquer 2007), and consequently, outcrossing seems to be a general trait for S. lophyropoda at the several spatial scales analysed (ranging from cm to 100s of km). However, the absence of inbreeding in this species with aggregated populations and short larval dispersal , Mariani et al 2006, although difficult to interpret, is in agreement with the conclusions of the several studies on other modular invertebrates, which report that restricted (both sexual and asexual) dispersal, strong population structure, and even consanguinity do not necessarily imply inbreeding depression (e.g. Grosberg 1987, Cohen 1990, Bishop & Ryland 1993, Jones et al 1994, McFadden 1997, Ayre & Miller 2006.…”
Section: Mating Systemsupporting
confidence: 89%
See 3 more Smart Citations
“…A significant absence of inbreeding also occurs in other geographically distant populations of this species (Blanquer 2007), and consequently, outcrossing seems to be a general trait for S. lophyropoda at the several spatial scales analysed (ranging from cm to 100s of km). However, the absence of inbreeding in this species with aggregated populations and short larval dispersal , Mariani et al 2006, although difficult to interpret, is in agreement with the conclusions of the several studies on other modular invertebrates, which report that restricted (both sexual and asexual) dispersal, strong population structure, and even consanguinity do not necessarily imply inbreeding depression (e.g. Grosberg 1987, Cohen 1990, Bishop & Ryland 1993, Jones et al 1994, McFadden 1997, Ayre & Miller 2006.…”
Section: Mating Systemsupporting
confidence: 89%
“…Our predictions on restricted dispersal in the species, based on its presumed philopatric larval behaviour , Mariani et al 2006, have been confirmed by autocorrelation statistics (Fig. 2), which detected the formation of pedigree structures.…”
Section: Spatial Population Structuresupporting
confidence: 73%
See 2 more Smart Citations
“…Sponges are sessile in their adult stage and exhibit low dispersal capabilities during their larval stage, due to the production of lecithotrophic larvae with a short life span and philopatric behaviour (Mariani et al, 2005(Mariani et al, , 2006Maldonado, 2006;Uriz et al, 2008). As in many other marine organisms, the reproductive timing in sponges is highly correlated with water temperature (see Riesgo & Maldonado, 2008 and references therein).…”
Section: Introductionmentioning
confidence: 99%